2021
DOI: 10.3390/oral1020014
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Allergies in Dentistry: A Cross-Sectional Study in a Group of French Dentists

Abstract: Background: Dentists have a high risk of developing occupational allergies due to their repeated exposure to many professional allergens. The aim of this cross-sectional study was to assess occupation-related allergies in a group of French dentists and to determine the main associated risk factors. Methods: A self-administered questionnaire about allergies, particularly occupational allergies, was published online in a private group dedicated to French dentists. Results: Data from 584 French dentists were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Common symptoms observed in these cases included occupational asthma, rhinitis, conjunctivitis, and laryngitis. Boudinar et al assessed the occupation-related allergies of 584 French dentists through a self-administered questionnaire and found that 50.3% of the participants had allergies and 13.4% had occupational allergies [ 35 ]. Unfortunately, dental professionals are often unaware of the allergenic potential of dental materials and lack vigilance.…”
Section: Dust-related Respiratory Diseases Of Dental Professionalsmentioning
confidence: 99%
“…Common symptoms observed in these cases included occupational asthma, rhinitis, conjunctivitis, and laryngitis. Boudinar et al assessed the occupation-related allergies of 584 French dentists through a self-administered questionnaire and found that 50.3% of the participants had allergies and 13.4% had occupational allergies [ 35 ]. Unfortunately, dental professionals are often unaware of the allergenic potential of dental materials and lack vigilance.…”
Section: Dust-related Respiratory Diseases Of Dental Professionalsmentioning
confidence: 99%